Incidental Arrhythmias During Atrial Fibrillation Screening With Repeat 7‐Day Holter ECGs in a Hospital‐Based Patient Population - Goulouti, Eleni; Lam, Anna; Nozica, Nikolas; Elchinova, Elena; Dernektsi, Chrisoula; Neugebauer, Felix; Branca, Mattia; Servatius, Helge; Noti, Fabian; Haeberlin, Andreas; Thalmann, Gregor; Kozhuharov, Nikola Asenov; et al. (Journal of the American Heart Association, 2024)
Screening for atrial fibrillation (AF) may reveal incidental arrhythmias of relevance. The aim of this study was to describe incidental arrhythmias detected during screening for AF in the STAR-FIB (Predicting SilenT AtRial FIBrillation in Patients at High Thrombembolic Risk) cohort study. In the STAR-FIB cohort study, we screened hospitalized patients for AF with 3 repeat 7-day Holter ECGs. We analyzed all Holter ECGs for the presence of the following incidental arrhythmias: (1) sinus node dysfunction, defined as sinus pause of ≥3 seconds' duration; (2) second-degree (including Wenckebach) or higher-degree atrioventricular block (AVB); (3) sustained supraventricular tachycardia of ≥30 seconds' duration; and (4) sustained ventricular tachycardia of ≥30 seconds' duration. We furthermore report treatment decisions because of incidental arrhythmias. A total of 2077 Holter ECGs were performed in 794 patients (mean age, 74.7 years; 49% women), resulting in a mean cumulative duration of analyzable ECG signal of 414±136 hours/patient. We found incidental arrhythmias in 94 patients (11.8%). Among these were sinus node dysfunction in 14 patients (1.8%), AVB in 41 (5.2%), supraventricular tachycardia in 42 (5.3%), and ventricular tachycardia in 2 (0.3%). Second-degree AVB was found in 23 patients (2.9%), 2:1 AVB in 10 (1.3%), and complete AVB in 8 (1%). Subsequently, 8 patients underwent pacemaker implantation, 1 for sinus node dysfunction (post-AF conversion pause of 9 seconds) and 7 for advanced AVB. One patient had an implantable cardioverter-defibrillator implanted for syncopal ventricular tachycardia. Incidental arrhythmias were frequently detected during screening for AF in the STAR-FIB study and resulted in device therapy in 1.1% of our cohort patients.